Fenomena Beling Malunan Sebagai Refleksi Kesetaraan Gender melalui Pembelajaran Ilmu Sosial - Bagus Weda Wigena, Ida; Arif Sobirin Wibowo; Komang Alit Wahyuni; Ida Bagus Arya Lawa Manuaba (IAIN Madura, 2025)
Beling malunan etymologically means “get pregnant first then get married”. Beling malunan is a form of adultery that is legalized in a hidden way. The main problem in this study is the increasing number of cases of beling malunan adultery that are legalized by society including the Brahmana dynasty which is considered the main social strata. The research purpose is to review the phenomenological meaning of beling malunan, then to embody the results of the analysis as a reflection of gender equality in social science learning. This qualitative study took subjects through purposive sampling, namely three Balinese konjugal families from the Brahmana dynasty. The data collection method used naturalistic interviews, document analysis, and FGD, with phenomenological analysis techniques. The research results showed that every family was happy when their child got beling malunan, Even beling malunan was intentional to test the psychological health and fertility. Beling malunan is an indicator of freedom from LGBT influence, save on medical examination costs, and can be a topic of social show-off to family and the local community. The values ​​that can be adopted from this phenomenon are values ​​that are reflective in nature to teach gender equality through social science learning.